A diálise peritoneal na vivência de familiares cuidadores - Cesar, Eliese Denardi (2013)
This study aims to know the experience of family caregivers responsible for the peritoneal dialysis procedure at home. Qualitative search conducted with eight family caregivers of patients who had peritoneal dialysis at home, linked to a clinic in Rio Grande do Sul. The data collection happened through a semi-structured interview between April and May 2009. The data was submitted to thematic analysis from which three categories emerged: conditions that impose the responsibility with peritoneal dialysis; the complexity of care; and the changes in the routine of family caregivers. The responsibility in the peritoneal dialysis procedure modifies meaningfully the life of family caregivers. It is up to the health professionals to seek strategies to work according to the patient’s and the caregiver’s reality with the purpose of minimizing the impact on these people’s lives.